Oil-price macroeconomic relationship in Australia and New Zealand: Application of hidden co-integration technique - Alom, Fardous (University of Malaya, 2014)
This study examines the relationships between oil prices and macroeconomic variables such as industrial/manufacturing production index, consumer price index, real effective exchange rates, lending rates and stock price index in Australia and New Zealand within the framework of hidden cointegration technique and crouching error correction model (CECM) of Granger and Yoon (2002) using updated data; the study hopes to contribute to the literature on oil price-macroeconomic relationship in the Asia Pacific region. The results suggest a weak or no evidence of long-run relationships between crude oil prices and macroeconomic variables in these countries with few exceptions. Positive changes in crude oil prices are found to influence the increase in consumer price indices in Australia and negative changes in crude oil prices found to be responsible for the long-run relationships with decrease in stock price indices and interest rates. The study fails to find any convincing evidence of the long-run relationship between oil price and New Zealand macroeconomic variables.